On the iconicity of Greek Mycenaean MA-KA (Alétheia - Estudos sobre Antiguidade e Medievo, 2019)
This paper analyses the relationship between the phonemes and the meanings of seven ancient Greek words which are formed from the Mycenaean (Linear B) syllables MA and KA. In this analysis, it considers the graphemic iconicity of the two syllables, within the Minoan and Mycenaean cultural context that was significantly linked with the worship of Mother Goddess throughout the lunar and solar cycles. The aim is to show that the differences between their meanings can be described as isomorphic to the differences between their phonemes, which, in turn, are depicted and/or justified in their graphemic iconicity. The paper concludes to the non-arbitrary relationship between the phonemes, graphemes and meanings of words, suggesting MA-KA as a historical marker.Key-words: language symbolism, Linear AB scripts, Mother Goddess